Effects of avermectin-B1 (MK-936) on the larval development of Chrysoperla externa (Hagen) (Neuroptera, Chrysopidae) - Ribeiro, Maria José; Matioli, José Claret; Carvalho, César Freire (Pesquisa Agropecuaria Brasileira, 2014)
Due to the importance of the lacewings as predators of eggs of agricultural pests and to determine preliminarly the viability of using avermectin-B1 (MK-936) insecticide in pest management programs, laboratory studies were undertaken to discover the interactions between different rates of the product and the pre-imaginal development of C. externa. The results obtained and statistically analyzed showed a negative linear regression between the increasing dosages of the product and the predator larval survival, therefore it was not considered important as an ovicide or harmful action of the insecticide on the larval stages of the insect, mainly at dosages of 0.1 - 0.4 ml/l. The insecticide applied directly on eggs reduced their incubation period and affected the duration of larval instares. However, the survival insects had a normal development. Dosages of avermectin-B1 over 0.4 ml/l applied to the eggs reduced the larval survival with a high mortality of the third instar larvae. This product at rates over 0.4 ml/l and malathion, diethion and fenthion insecticides had a strong contact action on the predator and the last three killed 100% of the new-born larvae. It was concluded that avermectin-B1 (MK-936) at dosages of 0.1 - 0.4 ml/l had not affected significantly the immature stages of C. externa and can be recommended in integrated pest management programs at places were the populations of this predator are in its pre-imaginal period.